1995
DOI: 10.1002/lsm.1900160208
|View full text |Cite
|
Sign up to set email alerts
|

HeNe laser therapy by fibroendoscopy in the mucosa of the equine upper airway

Abstract: Macroscopic and microscopic results indicated that laser treatment accelerated the cicatrization. Irradiated lesions cicatrized faster than control. These results suggest beneficial effects of low-level laser irradiation therapy on equine pharyngeal ulcerative lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…Few previous studies have analyzed histological variables in relation to their clinical relevance. As reported by others [21,22], the reduction of the extent of edema was an important early effect of laser therapy. Although Røynesdal et al [23] did not observe the prevention of early edema, it was a common event during this present study.…”
Section: Discussionmentioning
confidence: 74%
“…Few previous studies have analyzed histological variables in relation to their clinical relevance. As reported by others [21,22], the reduction of the extent of edema was an important early effect of laser therapy. Although Røynesdal et al [23] did not observe the prevention of early edema, it was a common event during this present study.…”
Section: Discussionmentioning
confidence: 74%
“…Gómez-Villamandos et al reported an increase in wound healing after laser therapy, with increased mitotic activity, number of fibroblasts, collagen synthesis and neovascularization of the injured tissues. 26 Other authors 16,27 observed that the production of fibroblast growth factors (FGF) and the predominance of fibroblasts in the culture increased considerably after low-intensity laser irradiation. Furthermore, Bisht et al reported the development of granulation tissue and epithelization of wounds in Wistar rats treated with He-Ne laser.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of the healing process is tissue biostimulation. Increase in ATP production and activation of mast cell, fibroblasts and lymphocyte causes anti-inflammatory and analgesia in patients 69,70 . The factors which affect the action of the laser are: duration of action, type of laser used and area exposed to the laser.…”
Section: Low-level Laser Therapymentioning
confidence: 99%